Kinetic and structural analysis of the ultrasensitive behaviour of cyanobacterial adp-glucose pyrophosphorylase - Gomez Casati, Diego Fabian (2000)
The kinetic and (supra)molecular properties of the ultrasensitive behaviour of ADP-glucose pyrophosphorylase (AGPase) from Anabaena PCC 7120 (a cyanobacterium) were exhaustively studied. The response of the enzyme toward the allosteric activator 3-phosphoglycerate (3PGA) occurs with ultrasensitivity as a consequence of the cross-talk with the inhibitor P1. Molecular 'crowding' renders AGPase more sensitive to the interplay between the allosteric regulators and, consequently, enhances the ultrasensitive response. In crowded media, and when orthophosphate is present, the activation kinetics of the enzyme with 3PGA proceed with increased co-operativity and reduced affinity toward the activator. Under conditions of ultrasensitivity, the enzyme's maximal activation takes place in a narrow range of 3PGA concentrations. Moreover, saturation kinetics of the enzyme with respect to its substrates, glucose 1-phosphate and ATP, were different at low or high 3PGA levels in crowded media. Only under the latter conditions did AGPase exhibit discrimination between low or high levels of the activator, which increased the affinity toward the substrates and the maximal activity reached by the enzyme. Studies of fluorescence emission of tryptophan residues, fourth-derivative spectroscopy and size-exclusion chromatography indicated that the ultrasensitive behaviour is correlated with intramolecular conformational changes induced in the tertiary structure of the homotetrameric enzyme. The results suggest a physiological relevance of the ultrasensitive response of AGPase in vivo, since the enzyme could be subtly sensing changes in the levels of allosteric regulators and substrates, and thus determining the flux of metabolites toward synthesis of storage polysaccharides.